Rancang Bangun Aplikasi Nota Otomatis Berbasis QR-Code Menggunakan PHP Framework Codeigniter Dan CSS Bootstrap - Pratama, Anggi Arif; Marzuki, Imam; Hikmah, Nuzul (INTRO : Journal Informatika dan Teknik Elektro, 2022)
A3-Comp is a store and service in the field of technology, one of which is engaged in sales and repairs. So far, sales transactions are still using the manual method, recording reports and notes provided is still manual. So that to carry out transaction activities is still quite slow and less efficient. Transaction notes are still written manually which are often faked by people who want to take more profit, so it is very detrimental to the store which has an impact on reducing customer trust. This process is considered very detrimental because it can deal with the law. Sales application with automated notes built using codeigniter and MYSQL framework. The purpose of the research conducted is to produce an information system to make sales transactions quickly and to avoid counterfeiting notes so as to facilitate the store in the transaction process.